Hepatic Insulin Resistance: A liver-specific type 2 diabetes - Andrade, Luis Jesuino de Oliveira (2024)
Introduction: The liver plays a critical role in glucose and lipid homeostasis. Insulin resistance (IR) has been increasingly recognized as a primary etiological factor in metabolic disorders. Hepatic insulin resistance (HIR) is a specific manifestation of IR characterized by the liver's reduced responsiveness to insulin despite elevated circulating insulin levels. Objective: This review aims to elucidate the role of HIR in the pathogenesis of metabolic disorders, focusing on its relationship with metabolic dysfunction-associated fatty liver disease (MAFLD) and type 2 diabetes mellitus (T2DM). Methods: A comprehensive literature search was conducted to explore the underlying mechanisms of HIR, its clinical implications, and its association with MAFLD and T2DM. Results: HIR is characterized by impaired insulin-mediated glucose uptake and increased hepatic glucose output. This metabolic dysfunction contributes to the development of hepatic steatosis, dyslipidemia, and insulin resistance in peripheral tissues. The interplay between HIR and lipogenesis is important in the progression of MAFLD and its association with T2DM, and could be described as a hepatic equivalent of T2DM. Conclusion: The understanding of a T2DM-like condition in the liver is decisive for developing more targeted and effective treatments.